Conclusion [in 2024 annual trends and outlook report] - Tadesse, Getaw; Glatzel, Katrin; Savadogo, Moumini (International Food Policy Research Institute, 2024)
African agrifood systems face several challenges and threats, both emerging and existing, that require concerted action and targeted policymaking by African governments and their partners. The 2024 edition of the Annual Trends and Outlook Report (ATOR) explores the challenges posed by the climate crisis to agrifood systems and the opportunities offered by a transition to a bioeconomy to mitigate and adapt to the adverse impacts of climate change. This edition of the ATOR seeks to support the development and subsequent implementation of the Comprehensive Africa Agriculture Development Programme (CAADP) through the renewed and updated post-Malabo CAADP agenda.